The shoulder’s hidden alarm: metastatic uterine leiomyosarcoma in disguise - S., Harshitha; Manjunath; Stephens, Jennifer B.; S., Sushmitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Uterine Leiomyosarcoma is a rare but aggressive soft tissue tumour arising from smooth muscle fibres of the uterus. Leiomyosarcoma is one of the most common types of smooth muscle-derived malignancies in uterus and it is an aggressive malignancy. We are reporting a unique case of a 54-year-old woman who presented with uterine leiomyosarcoma along with humeral metastasis manifesting as a right shoulder swelling, an uncommon site of metastasis. This case report emphasizes the rarity of this presentation and underscores the importance of thorough clinical and radiological evaluations in atypical presentations. This patient also had a significant symptom relief and improvement in quality of life following palliative care and chemotherapy.